Behavior of RC beam-column connections strengthened with externally bonded FRP composites / Hamid Sinaei - Hamid , Sinaei (2018)
The beam-column connections (BCCs) are the crucial part of RC framed structures intended to provide resistance to apply static or seismic load in plastic region. The majority of past published research has focused on the repair and retrofit of the RC framed BCCs using conventional methods like, concrete jacketing, steel jacketing, addition of external steel and fibre reinforced polymeric (CFRP) laminates. RC and steel jacketing have been the popular choices in areas with high seismicity, especially for RC columns applications. However, these processes are labor intensive and may be considered impractical in some cases as in case of interior joints with beams in two orthogonal directions. A practical way of controlling plastic hinging and implement the strong-column weak-beam concept is through the use of the CFRP retrofitting system. In order to successfully and effectively use the CFRP overlay technique, the mechanical behavior of the CFRP-RC needs to be understood and its response needs to be accurately predicted. The main focus of this research is strengthening of concrete BCC with the use of various configurations of CFRP sheet and plate, and investigates the load capacity and ductility of these connections using experimental and numerical investigations. A total of six (6) scaled-down RC exterior joints, comprising of a control specimen (non-retrofitted) and five (5) retrofitted specimens with different CFRP arrangements were tested under moderately monotonic loads. The retrofitted specimens include; BCC strengthened with two cross-shaped CFRP plates bonded at the joint (RCS2), BCC strengthened with two CFRP plates added to the top and bottom of the beam (RCS3), BCC reinforced at the top and bottom corners of the connection with L-shaped CFRP sheets (RCS4), BCC with two reinforcing CFRP plates on both sides of the beam web (RCS5), and a BCC wrapped with CFRP layers at some parts of the column close to the connection and at the end of beam (RCS6). In addition, accurate modeling of CFRP strengthened RC BCCs was conducted using finite element method (ABAQUS) and the exact details of its performance were verified with experimental results. After validating the accuracy of the numerical method, several parametric studies were carried out for CFRP reinforced samples, with different lengths and thicknesses in order to relocate the plastic hinge away from the face of the column. Two categories of samples were used. Samples reinforced with CFRP plates on both sides of the beam web and samples reinforced with CFRP plates on the upper and lower beam flanges. Both groups of samples were reinforced with CFRP plates in the web and flanges of the beam. The experimental results showed that the configuration of the CFRP had a different effect on the joint capacity and the connection ductility coefficient. The greatest effect on increasing the ductility factor was seen in the sample where two CFRP plates were used on both sides of the beam web (RCS5 sample). For the sample with the presence of CFRP plates at the top and bottom of the beam (RCS3 sample), the ductility factor was reduced, although the load capacity of this sample increased. Except for the RCS3 sample, the rest of the samples exhibited an increase in the ductility factor due to the CFRP reinforcement. In both groups, increasing the thickness of the reinforcing CFRP plates causes the effective length of these plates’ increases for the transfer of the plastic hinge. However, this increase is limited and excessive thickening may have a negative effect. The optimum effective length of the CFRP plate can be considered about twice the height of the beam from the exterior face of the column.